Investment Governance: Delegation Decision Antecedents by Insurance Companies in Kenya - M’Ariba, Rogers Kinoti; Oluoch, Oluoch (European Scientific Journal, ESJ, 2020)
t Delegation decisions comprise a key component of investment governance structures of firms. Based on agency theory, this paper explores corporate governance and market dynamics as antecedents of investment management delegation by insurance firms in Kenya. Investment governance structures employed by firms are shaped by their unique circumstances and diverse considerations. The objectives of this research were to establish the influence of corporate governance and market dynamics on the investment governance structures of insurance firms in Kenya. The study adopted a descriptive approach with a target population of forty six firms in insurance and reinsurance business in Kenya. Both primary data and secondary data were collected. Data analysis was conducted using STATA relying on a binary logistic regression model. The study found that shareholder control, board diversity and avoidance of agency problems leads firms towards delegating their investment management activities. Desire to access alternative assets, peer influences and asset allocation considerations had a lesser extent of influence on firms towards delegation. The study concludes that large shareholder dictations and lack of investment management expertise in boards causes firms to adopt delegation models in their investment management. On the other hand, easy access to investment markets and constant supply of high yielding government bonds pulls firms towards internal investment management. It isrecommended that firms make appropriate choices on extent of delegation by carefully evaluating their needs and developing structuresthat deliver best outcomes.